Sonic Detection - Collins, Rebecca; Linsley , Johanna (punctum books, 2026)
Sonic Detection is part sonic noir, part performance document, and part critical investigation of listening at the margins for readers interested in prospecting the boundaries of performance studies, sound studies, and interdisciplinary writing.The book opens with a group of sonic detectives (exact number unknown) who investigate the mystery of an as-yet-unidentified event that leaves traces only in the acoustic atmosphere. This hybrid fiction propels the reader up and down the UK coast and offers overheard fragments from a faded seaside resort, a container shipping port, a former coal-mining town, and the Scottish headquarters for North Sea oil. A heterogeneous collection of texts follows, from creative-critical essays, performance scores, engagement with the archives of earlier sonic detectives (including poet/performance artist Fiona Templeton and the sound art collective Bow Gamelan Ensemble), to a series of dispatches from expert witnesses with their ears to the ground. Sonic Detection is not so much a monograph as a polygraph, tongue-in-cheek associations with questionable forensic technologies firmly in place. The book emerges from a decade-long collaboration between artists Rebecca Collins and Johanna Linsley, who used eavesdropping as an expanded creative methodology. The project began as a series of hyper-local, community-based performance works in coastal locations in the UK (from Bournemouth to Aberdeen) and grew into an international, multi-disciplinary life work devoted to an ongoing, organized curiosity. Sonic detectives hold open a collective sonorous space. They are the embodiment of the phenomenophile, lingering longer in listening.